Heuristic twists and ontological creeds: road map for evolutionary economics - Ulrich Witt (Max Planck Institute of Economics, 2007)
What is special about the evolutionary approach? This question is given quite different, and partly incommensurable, answers in evolutionary economics. The present paper shows how the different answers correspond with, on the one hand, the particular heuristic twists by which the corresponding authors arrive at their hypotheses (e.g. by borrowing analogies from evolutionary biology). On the other hand, the answers hinge on different ontological assumption (i.e. on whether or not evolution in nature and in the economy are viewed as belonging to the same sphere of reality and, hence, as mutually dependent processes). By distinguishing these two dimensions a road map for evolutionary economics is drawn up that helps to better understand where, and why, the competing interpretations differ. In order to assess their achievements and their potential for future research, some results of an opinion poll among evolutionary economists are presented and discussed.
Keywords: 330; Evolutionsökonomik; Wissenschaftliche Methode; Theorie